Human capital and economic growth : the case of Barbados - Boamah, Daniel O. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2001)
Utilises a traditional production function framework to measure the contribution of human capital (education) to economic growth in Barbados over the period 1964-1993.